The Effect of Livelihood Capital on the Sustainable Livelihood of Rice Farmers in Penanggungan Village, Mojokerto Regency, East Java, Indonesia - Ma'ruf, Zulfan Firdaus; Syafrial, Syafrial; Suhartini, Suhartini (Universitas Panji Sakti, 2025)
Sustainable livelihoods are a crucial concept in efforts to achieve balanced social, economic, and environmental prosperity. In reality, many communities face challenges with their implementation, including uncertain income and limited access to existing resources. The existence of these problems necessitates effective strategies for achieving sustainable livelihoods. This research aims to analyze sustainable livelihood strategies by optimizing the livelihood capital owned by rice farmers. This research was conducted in Penanggungan Village, Trawas District, Mojokerto Regency. This research was conducted in February – March 2024. This research focused on farmers who grow rice plants, with 134 respondents. The method used is a sustainable livelihood approach based on livelihood capital. Data analysis used logistic regression. The results obtained from human capital, social capital, and physical capital have a significant and positive impact on sustainable livelihoods. Meanwhile, natural capital has no significant effect, and financial capital has a negative and insignificant impact on sustainable livelihoods. Thus, human capital, social capital, and physical capital have the opportunity to improve farmers’ sustainable livelihoods.